Determinantes De La Informalidad Laboral : Un Caso De Estudio En El Centro Histórico De La Ciudad De Santa Marta (2014-2020) (2022)
This document aims to find the determinants of labor informality: a case study in the historic center of the city of santa marta (2014-2020), for which reviews of different works that have been carried out by entities, institutions and organizations will be used in accordance with this social, economic problem. and cultural. Likewise, data will be brought from some surveys that will be carried out on the people who dedicate themselves to said activity, where aspects of health, education, housing, employment profile, the exodus of people, etc., that affect the creation and consolidation of labor informality in the area mentioned above. In order to find the factors that increase the incursion of people into informal employment, a recapitulation will be carried out according to the documents that will be reviewed and the different causes that the surveys to be carried out would show to know what correlations are presented between the two. sources of information that can explain in detail the genesis of the problem. According to the results, it could be concluded that the existence and prolongation of labor informality in the historic center of Santa Marta would be a consequence of the absence of public policies focused on the most vulnerable population that are reflected in social, cultural and economic aspects, such as they are: The low educational level, the precarious access to health systems, the high rates of migration, among others.